Estimasi Ukuran Bulir Mineral Magnetik pada Batuan Peridotit Berdasarkan Peluruhan Anhysteretic Remanent Magnetization (ARM) - Reida, Rina; Sudarningsih, Sudarningsih; Wianto, Totok (Jurnal Fisika FLUX, 2009)
A decaying measurement of Anhysteretic Remanent Magnetization(ARM) has been undertaken to estimation the grain size of magnetic mineralwhich carries remanent on peridotite igneous rocks. The samples are taken fromDesa Aranio, Kabupaten Banjar, South Kalimantan. The samples are taken in acylinder from with the diameter 2.54 cm and 2.2 cm in length by using Drill ModelD026-C. The giving, measuring and decaying process of ARM is done byMolspin AF Demagnetizer, partial Anhysteretic Remanent Magnetization(pARM), and Minispin Magnetometer. The estimation of grain size of magneticmineral is obtained by seeing ARM intensity decaying curve towards magneticfield shown by the samples of peridotite igneous rocks. The ARM intensitydecaying curve show that the estimated peridotite rocks in research aredominated by multidomain and the size are big, whereas the distribution of thegrain size is larger than 200 Î¼m.